Tectonic Strain in Sumatera Based on Continuous Sumatran GPS Array (SuGAR) Observation 2007-2008 - Rino, Rino; Meilano, Irwan; Hilman Natawidjaja, Danny (Indonesian Journal of Geospatial, 2012)
Abstract. Sumatra is located near the place where the collision between Indo-Australian Plate and Eurasian Plate heppened. When Indo-Australian Plate moves below Eurasian Plate, the friction that occur between both plates causes the strain is being accumulated. The strain that exceeds the elastic limit will be released as an earthquake. GPS observation in Sumatra was conducted to analyse the velocity of vector displacement and the heterogenous of tectonic strain on the surface as one of the tectonic indication to earthquake mitigation in the future. The result from data processing shows vector displacement in Sumatra has northeast direction that indicate inter-seismic and southwest direction that indicate post-seismic. The strain distribution is extension that indicate post-seismic equally scatteres dominantly in zone where happened Aceh earthquake on 2004, Nias earthquake on 2005, Bengkulu on Sptember 12th 2007, and earthquake on Mentawai Island on September 13th 2007. While strain as compression shows Sumatera still has inter-seismic effect.Keywords: compression, earthquake, extension, GPS.